2019
DOI: 10.3390/polym11020372
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement by Metallic Tube Filling of the Mechanical Properties of Electromagnetic Wave Absorbent Polymethacrylimide Foam

Abstract: By the addition of a carbon-based electromagnetic absorbing agent during the foaming process, a novel electromagnetic absorbent polymethacrylimide (PMI) foam was obtained. The proposed foam exhibits excellent electromagnetic wave-absorbing properties, with absorptivity exceeding 85% at a large frequency range of 4.9–18 GHz. However, its poor mechanical properties would limit its application in load-carrying structures. In the present study, a novel enhancement approach is proposed by inserting metallic tubes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Unlike empty honeycomb under L-direction (L-EH), the absorbent-foam-filled honeycomb ( Figure 4 a, L-FH-1) under L-direction exhibited foam-like features, i.e., the three typical regions, namely linear, plateau, and densification regions [ 38 ]. Figure 4 a shows that absorbent-foam-filling led to a significant reinforcement of the compressive performance, as compared with the empty honeycomb.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike empty honeycomb under L-direction (L-EH), the absorbent-foam-filled honeycomb ( Figure 4 a, L-FH-1) under L-direction exhibited foam-like features, i.e., the three typical regions, namely linear, plateau, and densification regions [ 38 ]. Figure 4 a shows that absorbent-foam-filling led to a significant reinforcement of the compressive performance, as compared with the empty honeycomb.…”
Section: Resultsmentioning
confidence: 99%
“…Typical specimens of empty honeycomb and absorbent-foam-filled honeycomb were shown in Figure 2 . The electromagnetic-wave absorption of the absorbent PMI foam and PLA 3D-printed honeycomb based on metamaterial absorber were measured in earlier studies [ 8 , 38 ]. The PLA 3D-printed honeycomb with resistive films and carbon-based absorbent PMI foam exhibited excellent electromagnetic-wave-absorption properties.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors demonstrated the efficient formation of conductive networks by using both types of fibers during foaming, resulting in specific EMI shielding effectiveness values from 10 to 60 dB. In the same way, Yan and co-workers [18] have considered the development of polymethacrylimide (PMI) foams with improved EMI shielding performance, focusing on EMI absorption, by adding electromagnetic absorbers during foaming, and combining said foam with metallic tubes to guarantee proper compressive performance, thereby creating a component that could find interesting applications in electromagnetic wave stealth load-carrying structural applications. Abbasi and co-workers [19] have developed microcellular polyetherimide (PEI) nanocomposite foams containing low amounts of graphene nanoplatelets, being able to reach high electrical conductivities while significantly reducing density, which could enable their use in cutting-edge sectors such as aerospace or telecommunications for applications requiring electrostatic discharge (ESD) or EMI shielding.…”
mentioning
confidence: 82%
“…The foam-filled corrugated panel has also been demonstrated to have enhanced blast resistance behavior compared with empty panels [31]. Besides foam filling, metallic [32][33][34] and composite [35,36] tubes are also effective in enhancing the strength and energy absorption of metallic foams [32], polymeric foams [33,35,36], and aluminum honeycombs [34]. In conclusion, foam filling and tube enhancement are two effective methods of increasing the specific strength and energy absorption of lattice and foam structures.…”
Section: Introductionmentioning
confidence: 88%